Positive pole piece, battery and electric equipment

By designing a multi-layer active material structure in the positive electrode sheet, the contradiction between liquid absorption capacity and circulation performance of the battery when improving compaction density is solved, and the high energy density and excellent circulation performance are achieved.

CN119812189AActive Publication Date: 2025-04-11BYD CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411364880.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-11
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

While improving the compaction density, existing batteries are difficult to take into account high liquid absorption capacity and excellent circulation performance, especially when the porosity of the electrode sheet is reduced and the electrolyte permeation path is extended.

Method used

By designing the first and second active material layers on both sides of the current collector in the positive electrode sheet, the thickness and particle size distribution thereof are controlled respectively, ensuring that the first active material layer has better liquid absorption capacity and the second active material layer has a higher compaction density.

Benefits of technology

The positive electrode sheet has both high compaction density and strong liquid absorption capacity, thereby improving the circulation performance and energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812189A_ABST
    Figure CN119812189A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a secondary battery and electric equipment. The positive pole piece comprises a current collector, a first active material layer and a second active material layer, the first active material layer and the second active material layer are stacked on the surface of at least one side of the current collector, the first active material layer is close to the current collector, and the first active material layer and the second active material layer independently comprise positive active materials. The thickness of the first active material layer is H1 [mu] m, and the thickness of the second active material layer is H2 [mu] m; the positive electrode active material in the first active material layer satisfies 0 < (D1Span + D1mo) * h1 < 2, the positive electrode active material in the second active material layer satisfies 2 < (D2Span + D2mo) * h2 < 6, h1 = H1 / (H1 + H2), and h2 = H2 / (H1 + H2). According to the positive pole piece provided by the invention, relatively high compaction density of the pole piece can be ensured, relatively good liquid absorption capability of the pole piece can also be ensured, and the cycle performance of a battery prepared from the positive pole piece is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to positive electrode sheets, secondary batteries and electrical equipment. Background Art

[0002] In order to improve the energy density of the battery, the method of increasing the compaction density is currently widely used to increase its volume energy density. As the compaction density increases, the electrode's liquid absorption capacity and the battery's cycle performance will decrease. At present, although the electrolyte can gradually infiltrate the electrode through vacuum injection, high-temperature aging, multiple injections and other methods, the closer to the inner layer of the electrode dressing, the longer the electrolyte penetration path, the greater the compaction density, and the more difficult it is to fully infiltrate. Summary of the invention

[0003] In view of this, the present application provides a positive electrode plate, a secondary battery and an electric device. The positive electrode plate provided in the present application can ensure both a high compaction density of the plate and good liquid absorption capacity of the plate, and the battery prepared therefrom has excellent cycle performance.

[0004] In a first aspect, an embodiment of the present application provides a positive electrode sheet, comprising a current collector and a first active material layer and a second active material layer stacked on at least one side surface of the current collector, wherein the first active material layer is arranged close to the current collector, the first active material layer and the second active material layer independently comprise positive electrode active materials, the first active material layer has a thickness of H1 μm, and the second active material layer has a thickness of H2 μm;

[0005] The positive electrode active material in the first active material layer satisfies 0<(D1 Span +D1 mo )*h1<2,

[0006] The positive electrode active material in the second active material layer satisfies 2<(D2 Span +D2 mo )*h2<6,

[0007] Among them, D1 Span :(D1 V90 -D1 V10 ) / D1 V50 , D2 Span :(D2 V90 -D2 V10 ) / D2 V50 , D1 mo is the most frequent particle size of the positive electrode active material in the first active material layer, D2 mo is the mode particle size of the positive electrode active material in the second active material layer, h1=H1 / (H1+H2), h2=H2 / (H1+H2).

[0008] In the positive electrode plate provided in the present application, by reasonably designing and formulating the particle size distribution of the positive electrode active material and regulating the thickness of the active material layer, the particle size and distribution of the material can be controlled, thereby regulating the compaction density of the plate and optimizing the liquid absorption capacity of the plate.

[0009] In the positive electrode provided in the present application, the liquid absorption capacity and lithium ion mobility of the first active material layer are better than those of the second active layer. The electrolyte first contacts the second active material layer. Although the liquid absorption rate of this layer is not as good as that of the first active material layer, the amount of electrolyte is sufficient at this time, which can also ensure that the electrode has a good liquid absorption capacity; as the infiltration path becomes longer, when it reaches the first active layer material layer, the electrolyte infiltration capacity gradually weakens, but the active material designed for this layer makes it have a higher liquid absorption capacity, so the electrolyte can still be well infiltrated, and the electrode has a strong liquid absorption capacity. At the same time, the positive electrode provided in the present application can make the compaction density of the first active material layer lower than the compaction density of the second active material layer. The electrolyte first contacts the second active material layer. Because the amount of electrolyte is sufficient and the path is short, the electrode also has a good liquid absorption capacity at a high compaction density. As the path becomes longer, when it reaches the first active material layer, the compaction density of the electrode is less than that of the first active material layer, so that the electrode can also be guaranteed to have a good liquid absorption capacity when the amount of electrolyte is small.

[0010] Therefore, the positive electrode plate provided in the present application not only ensures a high compaction density of the plate, but also ensures a strong liquid absorption capacity of the plate, and the lithium-ion battery prepared therefrom has excellent cycle performance.

[0011] The second aspect of the embodiment of the present application provides a secondary battery, including the positive electrode plate provided in the first aspect of the embodiment of the present application. Due to the use of the positive electrode plate provided in the embodiment of the present application, the secondary battery can have both good liquid absorption capacity and excellent cycle performance.

[0012] The third aspect of the embodiment of the present application provides an electric device, including the secondary battery provided by the second aspect of the embodiment of the present application. Since the secondary battery provided by the embodiment of the present application is used to power it, the electric device has a strong endurance and can have strong market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A schematic diagram of the structure of a cross section of a positive electrode sheet provided in one embodiment of the present application;

[0014] Description of the accompanying drawings: 1-positive electrode sheet; 10-current collector; 20-first active material layer; 30-second active material layer. DETAILED DESCRIPTION

[0015] With the rapid development of lithium-ion battery technology, improving battery performance to meet the growing demand for energy storage has become a research hotspot. Especially in electric vehicles and large-scale energy storage systems, the energy density, power density, cycle stability and safety of batteries are key indicators for measuring battery performance. However, traditional battery design often finds it difficult to take all these performance indicators into account at the same time, especially in the selection and preparation of cathode materials, where there are some contradictions and challenges.

[0016] In the background technology, in order to improve the energy density of the battery, researchers usually use the method of increasing the compaction density of the positive electrode material. Although this can increase the content of active substances per unit volume, it will also lead to a decrease in the porosity of the electrode sheet, a decrease in the penetration and absorption capacity of the electrolyte, thereby affecting the migration of lithium ions and the charge and discharge performance of the battery. In addition, high compaction density may also aggravate the volume expansion of the battery during the charge and discharge process, causing stress and rupture of the material structure, and affecting the cycle stability and life of the battery.

[0017] In order to solve these problems, researchers have tried a variety of methods, such as optimizing the composition, structure and preparation process of positive electrode materials, and using nanotechnology, carbon coating, ion doping and other means to improve the electrochemical properties of materials. Although these methods have improved battery performance to a certain extent, they still face challenges in cost, process complexity and large-scale production.

[0018] See also Figure 1 , the embodiment of the present application provides a positive electrode sheet 1, comprising a current collector and a first active material layer and a second active material layer stacked on at least one side surface of the current collector, the first active material layer is arranged close to the current collector, the first active material layer and the second active material layer independently include positive electrode active materials, the thickness of the first active material layer is H1μm, and the thickness of the second active material layer is H2μm;

[0019] The positive electrode active material in the first active material layer satisfies 0<(D1 Span +D1 mo )*h1<2,

[0020] The positive electrode active material in the second active material layer satisfies 2<(D2 Span +D2 mo )*h2<6,

[0021] Among them, D1 Span :(D1 V90 -D1 V10 ) / D1 V50 , D2 Span :(D2 V90 -D2 V10 ) / D2 V50, D1 mo is the most frequent particle size of the positive electrode active material in the first active material layer, D2 mo is the mode particle size of the positive electrode active material in the second active material layer, h1=H1 / (H1+H2), h2=H2 / (H1+H2).

[0022] In this application, D Span is the half-peak width of the particle size distribution of the positive electrode active material, defined as D Span :(D V90 -D V10 ) / D V50 .Dv 90 , Dv 50 and Dv 10 It is a parameter of the particle size distribution of the positive electrode material, representing the particle size when the cumulative value of volume distribution is 90%, 50% and 10%. 90 : The particle size when the cumulative value of volume distribution is 90%, which means that in the particle size distribution of the positive electrode material, 90% of the particle diameters are smaller than this value. 50 : The particle size when the cumulative value of volume distribution is 50%, that is, the median particle size or median diameter, which indicates the average particle size of the powder. 10 : The particle size when the cumulative value of volume distribution is 10% means that in the particle size distribution of the positive electrode material, only 10% of the particles have a diameter smaller than this value. These parameters provide important information about the particle size distribution of the positive electrode material, which is crucial to the physical and electrochemical properties of the reaction material. For example, Dv 90 and Dv 10 The gap can reflect the uniformity of the material, while Dv 50 It is often used to indicate the average particle size of powders, D Span It reflects the width of particle size distribution, that is, the degree of dispersion of particle size, D mo The most frequent particle size is the particle size with the highest frequency in the active material layer. In this application, for the convenience of description and distinction, the half-peak width of the particle size distribution of the positive electrode active material in the first active material layer is recorded as D1 Span , the particle size distribution parameter Dv of the positive electrode material 90 , Dv 50 and Dv 10 Denoted as D1v 90 , D1v 50 and D1v 10 , the most frequent particle size is recorded as D1 mo The half-peak width of the particle size distribution of the positive electrode active material in the second active material layer is recorded as D2 Span , parameter D2v of the particle size distribution of the positive electrode material 90 , D2v 50 and D2v 10 Denoted as D1v 90, D1v 50 and D1v 10 , the most frequent particle size is recorded as D1 mo

[0023] The smaller the Dv50 is, the smaller the particle size is, which helps to increase the specific surface area of ​​the material, thereby enhancing the liquid absorption capacity, accelerating the migration of lithium ions, and increasing the electrochemical reaction rate, while reducing stress concentration and improving the cycle stability and safety of the battery. mo Associated with a higher specific surface area, this not only enhances the activity of the electrochemical reaction and the ability to absorb liquid, but also helps to increase the migration rate of lithium ions, thereby improving the charge and discharge performance of the battery; in addition, D mo The consistency of Dv50 and D mo , D span , the size of material particles and their matching can be controlled, thereby achieving dense stacking between particles, increasing the compaction density of the material, and thus improving the energy density of the battery.

[0024] The first positive electrode active material layer satisfies the condition 0<(D1 Span +D1 mo )*h1<2, control the combination of the particle size distribution and the most frequent particle size of the positive electrode active material in the first positive electrode active material layer, and the thickness ratio in the positive electrode sheet, that is, (D1 Span +D1 mo )*h1 is less than 2, at which point the first positive electrode active material layer has better liquid absorption capacity, which is helpful for the penetration of electrolyte and the migration of lithium ions. At this point, the first active material layer has a higher compaction density, which helps to improve the charge and discharge capacity of the battery. Optionally, (D1 Span +D1 mo )The value of *h1 can be one of 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.5, and 1.8.

[0025] The second positive electrode active material layer satisfies the condition 2<(D2 Span +D2 mo )*h2<6, control the combination of the particle size distribution and the most frequent particle size of the positive electrode active material in the second positive electrode active material layer, and the thickness ratio in the positive electrode sheet, that is, 2<(D2 Span +D2 mo )*h2<6 is less than 2, in which case the second active material layer has a higher compaction density, which helps to improve the energy density of the battery. Optionally, (D2 Span +D2 mo)The value of *h2 can be one of 2.2, 2.5, 2.7, 2.9, 3.2, 3.5, 3.7, 3.9, 4.1, 4.3, 4.5, 4.9, 5.1, 5.5, and 5.7.

[0026] In this application, by controlling D mo and D Span The combination of h1 and h2, combined with the optimization of the thickness ratio of each active material layer, can achieve the regulation of the performance of the battery positive electrode material, which not only improves the liquid absorption capacity of the material, but also maintains a high compaction density of the positive electrode material, ensuring the performance of the battery at high energy density and high power density, while improving the battery's cycle stability.

[0027] In this application, D Span , D mo The test method of the value can be found in GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method, and the testing instrument is a laser particle size analyzer (such as Malvern 3000).

[0028] In the present application, the current collector of the positive electrode plate can be aluminum foil, carbon-coated aluminum foil, or other materials that can be used for current collectors.

[0029] In some embodiments of the present application, h1<h2. The thickness of the second active material layer is greater than that of the first active material layer, which can provide better liquid absorption capacity and faster lithium ion migration, and help improve the power performance and cycle stability of the battery.

[0030] In some embodiments of the present application, the thickness of the first active material layer satisfies 20 μm

[0031] ​In some embodiments of the present application, h2 / h1=(2-4). The first active material layer is close to the current collector, which is beneficial to improve the liquid absorption capacity and electrochemical reaction rate; while the thicker second active material layer provides additional storage capacity, while contributing to structural stability and battery cycle life. Optionally, the value of h2 / h1 can be 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.6, 4.0.

[0032] In some embodiments of the present application, 1<D1 Span <6,1<D2 Span <6,0.2μm<D1 mo <3μm, 0.2μm<D2 mo <3μm. In this application, D1 of the positive electrode active material is selected Span 、D2 Span Between 1 and 6, and D1 mo 、D2 mo The range of 0.2μm to 3μm is to comprehensively optimize battery performance. Moderate D1 Span 、D2 Span Ensure the consistency of particle size distribution, which helps to improve the cycle stability and reliability of the battery; and the appropriate D mo The range ensures sufficient specific surface area, promoting the activity of electrochemical reactions and liquid absorption capacity. This material selection balances the energy density and power density of the battery while taking into account cost-effectiveness, thermal management, mechanical strength and long-term stability of the battery.

[0033] In this application, the positive electrode active material has the structural formula of LiFe 1-x M x PO4, wherein 0≤x<1, M is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti. It can be understood that the positive electrode active material in the present application can be selected from doped or undoped lithium iron phosphate materials. Span and D mo The control of active thickness can improve the overall performance of the battery. In one embodiment, the positive electrode active material is selected from lithium iron phosphate.

[0034] In the present application, the first active material layer and the second active material layer also independently include a conductive agent and a binder, including a conductive agent and a binder, in the first active material layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (85-99): (1-14): (1-14); and / or, in the second active material layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (85-99): (1-14): (1-14). The conductive agent is selected from at least one of conductive carbon materials such as conductive carbon black, graphite, conductive ink, graphene, Ketjen black, acetylene black, carbon nanotubes, conductive carbon fibers, etc. The binder is selected from at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyolefins, SBR rubber, polyurethane, and related modified materials. The positive electrode active material layer design proposed in this application achieves comprehensive optimization of battery performance by adding a conductive agent and a binder to the first and / or second active material layer and controlling the mass ratio of the conductive agent and the binder to the positive electrode active material in the first and / or second active material layer within the range of (85-99):(1-14):(1-14). This composite ratio not only improves the conductivity and structural stability of the electrode, but also increases the cycle life and ensures process compatibility and cost-effectiveness.

[0035] It can be understood that in the present application, three or more active material layers may be provided on at least one surface of the current collector, and any two adjacent active material layers comply with the rules described in the present application and are within the protection scope of the present application.

[0036] In some embodiments of the present application, the preparation of the positive electrode sheet includes: S01, forming a first active material layer and a second active material layer stacked on the surface of the current collector. Specifically, the process of forming the positive electrode active material layer includes coating, and the specific coating process can be a process well known to those skilled in the art.

[0037] In the embodiment of the present application, the current collector may be any current collector suitable for the positive electrode of a lithium-ion battery, for example, aluminum foil or carbon-coated aluminum foil.

[0038] In some cases, a multilayer coating process, for example, a double-layer coating process, may be used. Specifically, a coating device capable of performing double-layer coating is used to simultaneously form a first active material layer and a second active material layer on the surface of the current collector. In other cases, the first active material layer and the second active material layer may be formed by sequentially coating the surface of the current collector.

[0039] In some embodiments of the present application, the first active material layer slurry includes but is not limited to a first solvent, a first binder, a first conductive agent, and a first positive electrode active material. The second active material layer slurry includes but is not limited to a second solvent, a second binder, a second conductive agent, and a second positive electrode active material. Among them, the first solvent and the second solvent can be reagents known in the art that are suitable for positive electrode slurry, including but not limited to N-methylpyrrolidone (NMP).

[0040] The embodiment of the present application also provides a secondary battery, including the aforementioned positive electrode plate provided in the embodiment of the present application. Due to the use of the positive electrode plate provided in the embodiment of the present application, the secondary battery can have both higher energy density and better cycle performance.

[0041] In the embodiment of the present application, the secondary battery may be a liquid secondary battery using a liquid electrolyte, a solid secondary battery using a solid electrolyte, a gel electrolyte, or a semi-solid secondary battery including both a solid electrolyte and a liquid electrolyte.

[0042] The present application also provides an electric device, including the secondary battery provided in the present application. Since the secondary battery provided in the present application is used to power the electric device, the electric device has a strong endurance and can have strong market competitiveness.

[0043] In some embodiments of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic equipment, power vehicles, energy storage systems, etc. Power vehicles include but are not limited to new energy vehicles, power-assisted bicycles, etc.

[0044] The technical solution of the present application is further illustrated by multiple embodiments below.

[0045] Example 1

[0046] (1) Screening of different D span And different D mo The positive electrode active material is lithium iron phosphate, a conductive agent, and a binder are added into a solvent N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5, and stirred to obtain a positive electrode slurry;

[0047] (2) coating the positive electrode slurry into a positive electrode sheet using a coating machine;

[0048] (3) The first active material lithium iron phosphate and the second active material lithium iron phosphate are prepared according to the above method. The thickness of the positive electrode sheet is 150 μm;

[0049] (4) Rolling the positive and negative electrode sheets, the compaction density of the positive electrode sheet can reach 2.73g / cm3;

[0050] (5) The positive electrode sheet and the negative electrode sheet (graphite: conductive agent carbon black: binder SBR = 90:5:5) are rolled and cut, and then the positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, and the stacked electrode cores are baked and assembled to form a soft-pack battery cell. Then, the soft-pack battery cell is prepared by liquid injection (the electrolyte is an organic solution of lithium hexafluorophosphate with a concentration of 1.0 mol / L, in which the solvent is EC:DMC:EMC with a mass ratio of 1:1:1), formation, aging, and sealing;

[0051] (5) Test the liquid absorption time of the positive electrode and the cycle capacity retention rate of the battery cell.

[0052] Embodiments 2 to 7

[0053] The method is basically the same as Example 1, except that the relevant parameters of the active material and the compaction of the electrode are different. The specific parameters are shown in Table 1.

[0054] Comparative Example 1-2

[0055] The method is basically the same as Example 1, except that the relevant parameters of the active material and the compaction of the electrode are different. The specific parameters are shown in Table 1.

[0056] Performance Testing

[0057] Compacted density test:

[0058] The coated electrode was rolled on a roller press at a pressure of 1 MPa, cut into small discs using a 30 mm sampler, and the mass and thickness were weighed, and the compaction density was calculated.

[0059] Absorption time:

[0060] Place the positive electrode in a glove box, inject 0.02 ml of electrolyte into the center of the electrode with a disposable syringe, start timing, and wait until the electrolyte is completely absorbed (no excess electrolyte is observed on the surface). Record this time as the absorption time.

[0061] Cycle capacity retention rate:

[0062] The prepared battery was charged and discharged at 25°C, with 1C constant current charging to 3.8V, constant voltage 3.8V charging to cut-off current 0.2C, and 1C constant current discharge to 2V; the above test system was cycled 1000 times, and the capacity retention rate was calculated. The average value of the two batteries was taken.

[0063] Table 1 Active materials and electrode parameters

[0064]

[0065] Table 2 Liquid absorption and cycle test results

[0066] Example Absorption time (s) Cycle retention rate @1000 times Example 1 369 95.20% Example 2 395 94.50% Example 3 425 92.00% Example 4 498 90.30% Example 5 560 89.20% Example 6 632 87.70% Example 7 785 85.40% Comparative Example 1 930 80.20% Comparative Example 2 1050 79.00%

[0067] According to the test data in Table 1 and Table 2, it can be seen that when the positive electrode active material in the first active material layer of the present application satisfies 0<(D1 Span +D1 mo )*h1<2, the positive electrode active material in the second active material layer satisfies 2<(D2 Span +D2 mo )*h2<6, the electrode has excellent liquid absorption capacity and battery cycle performance.

[0068] At the same time, by comparing Examples 1-6 with Example 7, it can be found that when h1 < h2 is satisfied, the liquid absorption capacity of the electrode and the battery cycle performance are further improved. Furthermore, when h2 / h1 = (2 to 4) is satisfied, the liquid absorption capacity of the electrode and the battery cycle performance are better. In this application, by controlling D1 mo 、D2 mo As well as D1 Span 、D2 Span The combination of h1 and h2, combined with the optimization of the thickness ratio of each active material layer, can achieve the regulation of the performance of the battery positive electrode material, which not only improves the liquid absorption capacity of the material, but also maintains a high compaction density of the positive electrode material, ensuring the performance of the battery at high energy density and high power density, while improving the battery's cycle stability.

[0069] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises a current collector and a first active material layer and a second active material layer stacked on at least one side of the current collector, wherein the first active material layer is arranged close to the current collector, the first active material layer and the second active material layer independently comprise positive electrode active materials, the first active material layer has a thickness of H1 μm, and the second active material layer has a thickness of H2 μm; The positive electrode active material in the first active material layer satisfies 0<(D1 Span +D1 mo )*h1<2, The positive electrode active material in the second active material layer satisfies 2<(D2 Span +D2 mo )*h2<6, Among them, D1 Span :(D1 V90 -D1 V10 ) / D1 V50 , D2 Span :(D2 V90 -D2 V10 ) / D2 V50 , D1 mo is the most frequent particle size of the positive electrode active material in the first active material layer, D2 mo is the mode particle size of the positive electrode active material in the second active material layer, h1=H1 / (H1+H2), h2=H2 / (H1+H2).

2. The positive electrode sheet according to claim 1, characterized in that: h1<h2.

3. The positive electrode sheet according to claim 2, characterized in that: h2 / h1=(2~4).

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: 20μm<H1<300μm, 20μm<H2<300μm.

5. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Satisfy: 1<D1 Span <6,1<D2 Span <6,0.2μm<D1 mo <3μm, 0.2μm<D2 mo <3μm.

6. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode active material has the structural formula of LiFe 1-x M x PO4, wherein 0≤x<1, and M is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti.

7. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode active material is lithium iron phosphate.

8. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: It includes a conductive agent and a binder, wherein in the first active material layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (85-99): (1-14): (1-14); And / or, in the second active material layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (85-99):(1-14):(1-14).

9. A secondary battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 1 to 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Nickel-cobalt-manganese compound particle powder and method for producing same, lithium composite oxide particle powder and method for producing same, and nonaqueous electrolyte secondary battery

    CN102574700A

  • Cathode active material, cathode plate and lithium ion secondary battery

    CN110518232A

  • Positive electrode active material, positive plate and lithium ion battery

    CN115312763A

  • Lithium ion battery positive plate and lithium ion battery

    CN116435466A

  • Lithium-rich manganese-based positive electrode material and preparation method thereof, positive electrode plate and secondary battery

    CN118538880A